2011
DOI: 10.1007/s11250-011-9888-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distribution of cattle anthrax outbreaks in Zimbabwe between 1967 and 2006

Abstract: This retrospective study aimed to assess the spatial and temporal distribution of anthrax and to identify risk areas in Zimbabwe. The data were extracted from the monthly and annual reports of the Division of Livestock Production and Veterinary Services for the period 1967 to 2006. The data were analyzed in relation to temporal and spatial factors. The hot-dry season was found to be significantly (X 2 = 847.8, P< 0.001) associated with the occurrence of anthrax in cattle and the disease was found to be approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 15 publications
7
39
0
Order By: Relevance
“…In support of earlier observations on cattle anthrax outbreaks in Zimbabwe (Chikerema et al 2012), cattle owners indicated that anthrax is a hot-season disease. Focus group discussions revealed cattle owners' observations on an increased trend of cattle anthrax outbreaks, which they attributed to cessation of government-sponsored annual cattle vaccinations that used to be conducted by the government.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In support of earlier observations on cattle anthrax outbreaks in Zimbabwe (Chikerema et al 2012), cattle owners indicated that anthrax is a hot-season disease. Focus group discussions revealed cattle owners' observations on an increased trend of cattle anthrax outbreaks, which they attributed to cessation of government-sponsored annual cattle vaccinations that used to be conducted by the government.…”
Section: Discussionsupporting
confidence: 73%
“…On the basis of the mean number of outbreaks per district, mean number of years of occurrence, and mean number years of recurrence of cattle anthrax outbreaks over a 40-year period (1967-2006), administrative districts in Zimbabwe have been classified as high-, medium-, and low-risk anthrax districts (Chikerema et al 2012) (Fig. 1).…”
Section: Study Location and Selection Of Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of anthrax outbreaks within a particular locality tend to have a seasonal signal, although the season during which most cases occur varies from locality to locality. Outbreaks consisting primarily of grazing wildlife or livestock occur in seasonal or weather conditions along a spectrum from drought (Fox et al 1977, Shiferaw et al 2002, Muoria et al 2007, Wafula et al 2008, Hampson et al 2011, to hot dry seasons often following years of unusually high rainfall (Rees et al 1977, Gates et al 1995, Dragon et al 1999, Turner et al 1999, Himsworth and Argue 2008, Chikerema et al 2012, to transition periods between dry-wet or wet-dry conditions (Fox et al 1973, Parkinson et al 2003, Siamudaala et al 2006, Mongoh et al 2008, to wet season outbreaks (Lindeque and Turnbull 1994, Durrheim et al 2009, Chikerema et al 2012. Some authors do not specify the time scale in which the described weather patterns occur in relation to the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, during 1995-2005, a total of 282 outbreaks and 2978 animal cases (livestock and wildlife) were reported [16]. Anthrax is one of the major threats to animals and humans in the Western part of Zambia, in 2010, it affected 45 cattle and three humans [17].…”
Section: Introductionmentioning
confidence: 99%